Direct Time Domain Numerical Analysis of Transient Behavior of a VLFS during Unsteady External Loads in Wave Condition. (16th July 2014) - Cheng, Yong; Zhai, Gang-jun; Ou, Jin-ping
Abstract : The transient response of the VLFS subjected to arbitrary external load is systematically investigated by a direct time domain modal expansion method, in which the BEM solutions based on time domain Kelvin sources are used for hydrodynamic forces. In the analysis, the time domain free-surface Green functions with sufficient accuracy are rapidly evaluated in finite water depth by the interpolation-tabulation method, and the boundary integral equation with a quarter VLFS model is established taking advantage of symmetry of flow field and structure. The validity of the present method is verified by comparing with the time histories of vertical displacements of the VLFS during a mass drop and airplane landing and takeoff in still water conditions, respectively. Then the developed numerical scheme is used in wave conditions to study the combined action taking into account the mass drop/airplane landing/takeoff loads as well as incident wave action. It is found that the elevation of structural waves due to mass drop load can be significantly changed near the impact region, while the vertical motion of runway in wave conditions is dominant as compared with that only generated by airplane.